HADITH STUDIES ON THE IDDAH AND IHDAD OF WOMEN PUBLIC OFFICIALS: An Integration of Normative and Empirical Studies - Wakhidah, Nur; Hamdi, Fahmi; Sholihah, Mida Mar'atus; Subakir, Ahmad (RIWAYAH, 2024)
Iddah and ihdad are sharia commanded by Allah, and they have the value of worship. While female public officials are bound by the rules of employment. This study seeks to normatively and empirically analyze the hadiths about iddah and ihdad. The study of iddah and ihdad is dynamic, necessitating collaboration on normative and empirical hadith studies. The research data can be analyzed using various theories, including normative and empirical hadith understanding, public policy theory, justice theory, and maslahah theory. We obtained the data through literature, interviews, and observation methods. The study’s results demonstrated the integration of normative and empirical hadith studies. The typology of hadith studies is becoming increasingly complex, necessitating the elaboration of normative and empirical studies while adhering to the principles of hadith studies.[Iddah dan ihdad merupakan syari’at yang diperintahkan Allah dan memiliki nilai ibadah. Sementara wanita pejabat publik terikat dengan aturan kepegawaian. Penelitian ini bertujuan untuk menganalisis hadis-hadis tentang iddah dan ihdad secara normatif dan empiris. Kajian iddah dan ihdad mengalami sebuah dinamika, sehingga kajian tersebut perlu mengkolaborasi studi hadis normatif dan empiris.  Beberapa teori untuk menganalisis data penelitian adalah teori pemahaman hadis normatif dan empiris, teori kebijakan publik, teori keadilan, dan teori maslahah. Data diperoleh melalui metode Pustaka, wawancara dan observasi. Hasil penelitian ini menemukan integrasi kajian hadis normatif dan empiris. Tipologi kajian hadis dengan arah kajian semakin kompleks, perlu elaborasi kajian normatif dan empiris dengan tetap memelihara prinsip-prinsip kajian hadis.]